A Case Study on Teaching English with Differentiated Instructions at a Junior High School in Taiwan - Abdul Halim; Sunarti; Ibrahim (Universitas Islam Negeri (UIN) Mataram, 2022)
The article aims to explore a case of teaching with differentiated instructions approach at a Junior High School, Eastern County, Taiwan. The author used case study as the interpretivism paradigm in the methodology of exploring the contexts. The participants were twenty-five 12 graders. They were assigned by the school academic director to participate in the classroom demonstration on differentiated instruction with one of the senior teacher trainers from Taipei City. Pre-observation interview, observation, and post-observation interview were utilized to collect the data. The study indicated that a well-planned lesson for differentiated instruction would be able to help mixed-ability students get most of the lessons. Furthermore, it can also enhance the student’s engagement during the lesson in the classroom. Some suggestions for further research are proposed.